Inclusive Education: A Step towards Development of Right Based Society - Prerna Baria (Journal of Learning and Educational Policy, 2023)
Education is considered as human right in various national and international conferences. The same is reflected even in our constitution under different provisions. We consider “Education as a powerful instrument to bring social changes, and often initiates upward movement in the social structure”. Every individual is equally responsible for the positive as well as negatives changes taking place in the society, so in a democratic set-up, its citizen must be necessarily educated for the improvement of human society. The concept of inclusive education is being misunderstood by many as it is only about disabled children but in fact, it is not confined to the disabled. It also means non-exclusion. Inclusive education, is about embracing all. It has given rise to the concept of respect for an inherent dignity of all human beings. Under all human beings concept, the active and full participation of the people in the society irrespective of their characteristics is emphasized. Inclusive education refers to “to all learners, young people with or without appropriate network of support services”. Now a days it has become necessary to develop sense of social acceptance and inclusion with supportive environment to diverse learners. Now we have realized the importance of education and striving hard to provide access to education to the entire population, hence change in the attitude of communities, school and government about the right meaning of inclusive education is an important step for making Inclusive society. For the society to be inclusive, it is required to equip disabled learners who ultimately are the part of society with skills, tools and guidance they need to earn a living and lead an independent and happy life. To overcome the incongruous situation, we all have to create an environment to make our society aware about free of discrimination. Here the meaning, need and challenges faced while implementation of inclusive education is elaborate.